Copy number variants in attention-deficit hyperactive disorder: identification of the 15q13 deletion and its functional role. (April 2015) - Valbonesi, Stefano; Magri, Chiara; Traversa, Michele; Faraone, Stephen V.; Cattaneo, Annamaria; Milanesi, Elena; Valenti, Vera; Gennarelli, Massimo; Scassellati, Catia
Abstract : Objectives: Evidence has supported a role for rare copy number variants in the etiology of attention-deficit hyperactivity disorder (ADHD), in particular, the region 15q13, which is also a hot spot for several neuropsychiatric disorders. This region spans several genes, but their role and the biological implications remain unclear. Methods: We carried out, for the first time, an analysis of the 15q13 region in an Italian cohort of 117 ADHD patients and 77 controls using the MLPA method, confirmed by a genome single-nucleotide polymorphism array. In addition, we probed for downstream effects of the 15q13 deletions on gene expression by carrying out a transcriptomic analysis in blood. Results: We found 15q13 deletions in two ADHD patients and identified 129 genes as significantly dysregulated in the blood of the two ADHD patients carrying 15q13 deletions compared with ADHD patients without 15q13 deletions. As expected, genes in the deleted region ( KLF13, MTMR10 ) were downregulated in the two patients with deletions. Moreover, a pathway analysis identified apoptosis, oxidation reduction, and immune response as the mechanisms that were altered most significantly in the ADHD patients with 15q13 deletions. Interestingly, we showed that deletions in KLF13 and CHRNA7 influenced the expression of genes belonging to the same immune/inflammatory and oxidative stress signaling pathways. Conclusion: Our findings are consistent with the presence of 15q13 deletions in Italian ADHD patients. More interestingly, we show that pathways related to immune/inflammatory response and oxidative stress signaling are affected by the deletion of KFL13 and CHRNA7 . Because the phenotypic effects of 15q13 are pleiotropic, our findings suggest that there are shared biologic pathways among multiple neuropsychiatric conditions.